Legislation and institutional practices concerning compensation for victims of rape in Denmark - Johansen, Louise Victoria (International journal of law, crime and justice, 2025)
This article investigates the framework for compensating rape victims in Denmark, focusing on the interplay between legislation, victim lawyers' roles, and institutional practices, particularly those of the Victim Compensation Board (VCB). Grounded in legal, qualitative, and quantitative analyses, I focus specifically on the roles of victim's lawyers and the Victim Compensation Board in relation to victims and examine the levels of compensation awarded to victims of rape in the years between 2013 and 2021, as well as the reasons given by the Board to qualify its decisions. Two primary points of analysis are addressed: first, the role of victim lawyers in supporting rape victims during the legal process and its impact on compensation outcomes; second, the influence of societal and legal constructs of rape—specifically the distinctions between stranger, contact, and partner rape—on compensation levels and reporting patterns. The study addresses the lack of legal representation for victims at the VCB stage, which often leads to reduced compensation, particularly in complex categories like permanent injuries and lost earnings. It also examines how the new Consent Act on rape from 2020, while increasing reporting rates, has not improved conviction rates regarding the crime or significantly altered compensation practices, which remain influenced by outdated notions of coercion and visible injury. By highlighting these issues, the article argues for more transparent guidelines and extended legal aid to align Denmark's practices with international human rights obligations.